Still not allowed on the bus: It matters if you're black or white! - Redzo Mujcic; Paul Frijters (Institute for the Study of Labor (IZA), 2013)
We employ a natural field experiment to study the extent and nature of racial discrimination in Queensland, Australia. Mimicking the historical case of Rosa Parks who was denied seating in a bus because she was black, an important moment for the U.S. civil rights movement, we sent trained testers who differed in ethnic appearance to bus stops asking the driver for a free ride on the basis that their bus pass was faulty (which it was). In total, we obtained 1,552 observations of testers either allowed a free ride or not, in each case recording the characteristics of the bus driver, the tester, and the circumstances. We find strong evidence of discrimination against black-skinned individuals. In the baseline scenario, white testers were accepted during 72% of the interactions versus only 36% for black testers. Indian testers were let on 51% of the time and Asian testers (mainly Chinese) were let on 73% of the time. Favors were more likely to be granted when the bus driver and tester were of the same ethnicity, and when there were fewer people in the bus. Patriotic appearance matters in that testers wearing army uniforms were accepted at a rate of 97% if they were white and 77% if they were black. Status appearance also mattered in that black testers dressed in business attire were just as likely to be favored as casually dressed white testers. When bus drivers were confronted with hypothetical baseline scenarios using photos taken of the real testers, 86% responded they would let on the black individual, more than double the actual number accepted, indicating dishonest self-reporting on this topic.
Keywords: C93; J15; J71; D03; 330; racial bias; discrimination; natural field experiment; prosocial behavior